Product trustworthy consumer reaction to product recalls / Hasneezah Abd Rashid - Abd Rashid, Hasneezah (Faculty of Business and Management, 2014)
The number of product recalls has been increasing in recent years worldwide. Several studies have tried to define the best ways for the companies to manage product recalls and to mitigate negative impacts on brand image. However these efforts mostly adopt a managerial perspective, thus largely ignoring the customers’ point of view. The experimental study investigated three factors that may affect consumer perceptions of companies making product recalls. When information indicating that the company acted in a socially responsible manner was present, student consumers held more favorable feelings toward the company. A government press release was viewed as more objective than a company advertisement discussing the recall. Finally, the print medium was viewed as more trustworthy and somewhat more objective than the sound medium. Managerial implications are provided. A quasi-experiment is conducted on a sample of 50participants in order to analyze customers’ reaction to the communication activated by the company. Findings underline the impact of responsible vs. opportunistic recall management and partly disconfirm previous results about the moderating role of brand reputation.